Preparation of thin coatings of titanium compounds with ion implantation - Mozetič, Miran (Informacije MIDEM, 1999)
The growth of thin coatings of titanium oxide and nitride during ion implantation of respective ions into titanium substrate was studied theoretically and experimentally. The IBM SRIM software was used to determine the concentration profiles of implanted ions, the sputtering rate, probability of back - scattering and ion energy loss mechanisms. Theoretical results were compared with experiments. Samples of pure titanium plates were carefully polished and exposed to a flux of oxygen and nitrogen ions with the kinetic energy of 100 keV per molecule (50 keV per atom). The ion doses were 5x10sup16, 1x10sup17, 2.5x10sup17, 5x10sup17, 7.5x10sup17, 1x10sup18 atoms/cmsup2. Depth profiles of the samples were determined by the AES method. Both the theory and experiment showed that the ion range at the low dose was about 90 nm for the case of nitrogen, and 80 nm for the case of oxygen, with depth distribution typical for ion implantation. Experimental results showed that a layer of titanium compound with a constant composition was formed at the ion dose above 7.5x10sup17 atoms/cmsup2.
Keywords: implantacija; ioni; mikroelektronika; površine; tanke plasti; titanov dioksid